Variation in egg size of the fresh-water prawn Macrobrachium amazonicum (Decapoda: Palaemonidae) - Odinetz Collart, O. (1996)
Egg size of the fresh-water prawn Macrobrachium amazonicum varied among ecologically isolated or geographically distant populations of the Amazon basin. The mean volume of both recently spawned nonpigmented eggs and older pigmented eyed eggs was smaller in prawns from the Tocantins River (0.14 and 0.20 mm3, respectively) than in those from the middle Amazon (0.17 and 0.25 mm3). The largest eggs (0.19 and 0.27 mm3) were displayed by females from the Iquitos and Guapore Rivers. Since the egg volume was independent of female body size, it was attributed to population specific characteristics. The egg size increased with the distance of the sampling site from the ocean, suggesting a progressive divergence of this species from a typical littoral population to an inland form, in a still active fresh-waterization process similar to the pattern evolved among other species in the genus Macrobrachium.